Dynamic response of a vibrated fluidized bed of fine and cohesive powders - Barletta, Diego; Russo, Paola; Poletto, Massimo (Powder technology, 2013)
The dynamics of a fully fluidized bed of group A and group C powders subject to vertical vibration was studied in an 85mm ID transparent perspex column. Acceleration level was set to a/g=1 and 2 respectively for the two powders. Frequency was varied in the range between 5 and 60Hz. Different bed mass values corresponding to different bed heights were tested. Time series of the position of the oscillating column wall and those of the oscillating bed height were obtained by means of particle image velocimetry applied to sequences of digitized images of the bed taken by means of a high speed video camera. These time series were used to study the dynamics of the bed surface as a function of the imparted oscillation. A simple model based on a pseudo homogenous approach, assuming the bed as a linear elastic continuum subject to viscous damping, was developed to calculate theoretical values of amplitude ratio and phase lag. Bode diagrams obtained by plotting the experimental values of the amplitude ratio and phase lag were used to fit the two model parameters: the elastic wave velocity and the viscous dissipation coefficient. Comparison between model and experiments is fairly good in terms of phase lag. The model amplitude ratio, instead, fails to exactly describe the experiments close to the natural resonance frequencies of the system at which larger ratios are expected and generally found. In particular, for the group A powder the oscillation of the particulate phase is more complicated than predicted due to the appearance of multiple concentration fronts close to the bed surface. The fitted elastic wave velocity is in close agreement with the equation proposed by Roy et al. (Chem. Eng. Sci, 45, 1990, 3233–3245). A new proposed model for the viscous damping coefficient based on wall friction interaction between the bed of powders and the column is able to predict satisfactorily the experimental data. [Display omitted] ► The dynamic response of a Geldart group A and C fluidized powders was studied. ► Column and bed surface motion was recorded with a high speed camera and studied. ► Experimental Bode diagrams were derived and compared with a viscous-elastic model. ► Sound velocities are well predicted by a simple pseudo homogeneous model ► A predictive expression for viscous damping based on wall friction is proposed.